THE SPEECHES AND PARADOXES OF HUMAN RIGHTS - Miguez, Aline Bastos Lomar; D'Almeida, Alexandre Pedro Moura (Unoesc International Legal Seminar, 2017)
Human rights reveal contradictory argumentation. The network of values that has been produced is based on the fiction of the existence of universal content, which reveals the desire for a single foundation. However, the crystallized conceptual plot is insufficient to encompass the dual character of the human being’s right. Making concepts malleable, showing clearly their antagonisms, enables adjustments and resistance to the actives forces. The purpose of this article is to analyze the human rights contradictions concerning its scope, language and ideals, revealing the movement that makes it possible both social emancipation and the instrumentalization for control. The method utilized in the present work consists of a literature review, conceptual review and an approach of concepts. The results demonstrate that the discourses of human rights are linked to the historical and political situation of each place and it is clear that its use is not always linked to the effective defense of man.